ECONOMIC DIPLOMACY AS CHINA’S STRATEGY IN THE ARCTIC REGION TO SUPPORT THE POLAR SILK ROAD INITIATIVE - Agniyah, Nida Nuril; Rahmadan, Yanuar (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This study analyzes China's strategic implementation of economic diplomacy in the Arctic region to support the Polar Silk Road (PSR) initiative, an integral part of the Belt and Road Initiative (BRI). Although China is not geographically an Arctic state, it claims the status of a